Spectrum of Uveitis in A German Tertiary Center: Review of 474 Consecutive Patients. (August 2015) - Grajewski, Rafael S.; Caramoy, Albert; Frank, Konrad F.; Rubbert-Roth, Andrea; Fätkenheuer, Gerd; Kirchhof, Bernd; Cursiefen, Claus; Heindl, Ludwig M.
Abstract Purpose: To analyze the spectrum of uveitis at a German tertiary center. Patients and methods: A total of 474 consecutive patients with uveitis were classified according to the primary anatomic site of inflammation, examined for laterality of disease, and screened for etiologies. Results: Out of the total, 253 patients (53%) had anterior uveitis, 90 patients (19%) had intermediate uveitis, 100 patients (21%) had posterior uveitis, and 31 patients (7%) had panuveitis. Fifty-six percent of the patients had bilateral involvement, predominantly in intermediate uveitis (ratio 4:1) and panuveitis (ratio 3.4:1). Regarding the etiology of all uveitis cases we found 17% infectious, 23% specific clinical entities, 20% associated with systemic disease (most commonly sarcoidosis with 11%), and 41% idiopathic uveitis. Conclusions: Anterior uveitis was the most common anatomic site of intraocular inflammation. Using a tailored approach, screening for systemic etiologies is recommended, since 20% of all patients had associated systemic diseases.